Impact of Cardiovascular Magnetic Resonance Imaging on Identifying the Etiology of Cardiomyopathy in Patients Undergoing Cardiac Transplantation. Issue 1 (December 2018) - Lin, Lucy; Kazmirczak, Felipe; Chen, Ko-Hsuan; Okasha, Osama; Nijjar, Prabhjot; Martin, Cindy; Akçakaya, Mehmet; Farzaneh-Far, Afshin; Shenoy, Chetan
Abstract Errors in identifying the etiology of cardiomyopathy have been described in patients undergoing cardiac transplantation. There are increasing data that cardiovascular magnetic resonance imaging (CMR) provides unique diagnostic information in heart failure. We investigated the association of the performance of CMR prior to cardiac transplantation with rates of errors in identifying the etiology of cardiomyopathy. We compared pre-transplantation clinical diagnoses with post-transplantation pathology diagnoses obtained from the explanted native hearts. Among 338 patients, there were 23 (7%) errors in identifying the etiology of cardiomyopathy. Of these, 22 (96%) occurred in patients with pre-transplantation clinical diagnoses of non-ischemic cardiomyopathy (NICM). Only 61/338 (18%) had CMRs prior to transplantation. There was no significant association between the performance of CMR and errors in the entire study cohort (p = 0.093). Among patients with pre-transplantation clinical diagnoses of NICM, there was a significant inverse association between the performance of CMR and errors (2.4% vs. 14.6% in patients with and without CMR respectively; p = 0.030). In conclusion, CMR was underutilized prior to cardiac transplantation. In patients with pre-transplantation clinical diagnoses of NICM – in whom 96% of errors in identifying the etiology of cardiomyopathy occurred – the performance of CMR was associated with significantly fewer errors.